DIRECT – REDUCTION OF COUNTRY RISKS IN ATTRACTING FOREIGN DIRECT INVESTMENT (European Journal of Economics, Finance and Business Development, 2025)
The article reveals ways to reduce the country's risks in attracting foreign direct investment. Also, ways of guaranteeing foreign investors by KTIKA (multilateral investment guarantee agency) to investors and creditors have been studied by international organizations. Among other international organizations (Special Foreign Investment Company, Organization for Economic Cooperation and Development), ways of assessing project risks based not only on economic criteria, but also on socio-ecological criteria have been researched.